Traducciones múltiples: la superación de la egestas en Manilio (Argos, 2025)
This paper analyzes the contest between the Latin and Greek languages regarding the technical terminology of astrology and the names of some constellations in M. Manilius' Astronomica. This contest is compared to the ideological qualifications of the national longue. The conclusion is that, although Manilius depended on Greek sources for the composition of his poem, he has written a typically Roman work where the variety of vocabulary and of procedures available to translate the concepts, outweighs the traditional topic of egestas linguae latinae.
Keywords: Manilius; egestas; astrology; latin; greek